Project Acceleration By Time and Cost Optimization at PT. Dui Esa Unggul With CPM & Pert Method - Arif Budi Sulistyo; Irfanul Muhaimin (Jurnal Syntax Transformation, 2023)
Projects are activities that are temporary in nature, have deadlines, budgets, resources and have product specifications to be produced. The case study of this research is the Matarbari Throat Ring Unit-2 fabrication project carried out by PT. Dui Esa Superior . The purpose of this study is to determine the factors that cause project delays, and to find out how long the duration and the optimal cost for the project are. The methods used are FTA (Fault Tree Analysis), CPM (Critical Path Method), and PERT (Project Evaluation and Review Technique). The results of direct field observations and interviews, as well as analysis and evaluation using the FTA, CPM and PERT methods, obtained 19 basic event factors causing project delays, namely labor shortages, workers lack of understanding of drawings, bad weather / rain , and others. There are 9 basic event combinations or minimum cut sets, namely (D1*D2*D3), (D4*D5), (C3), (D6), (E1*E2), (E3*E4*E5), (F1 ), (F2*F3*F4), (F5*G1*G2). The optimal duration of the Matarbari Throat Ring Unit-2 project is 57 days from the normal 61 days with a 69.15% chance. The total optimal cost of the Matarbari Throat Ring Unit-2 project with the optimal duration is Rp. 127,772,400.